Copy number variations in the GATA4, NKX2‐5, TBX5, BMP4 CRELD1, and 22q11.2 gene regions in Chinese children with sporadic congenital heart disease. Issue 2 (17th September 2018) - Li, Zhetao; Huang, Jiwei; Liang, Biao; Zeng, Dingyuan; Luo, Shiqiang; Yan, Tizhen; Liao, Fengwen; Huang, Jun; Li, Jingwen; Cai, Ren; Deng, Xine; Tang, Ning
Abstract : Background: Congenital heart disease (CHD) is a common birth defect originating from both environmental and genetic factors. An overabundance of copy number variations (CNVs) affecting cardiac‐related genes has previously been detected in individuals with CHD. Objective: To evaluate if the presence of CNVs in the 22q11.2 region, and to determine whether GATA4, NKX2‐5, TBX5, BMP, and CRELD1 genes contributed toward the pathogenesis of isolated incidences of CHDs in southwest China. Methods: In total 167 patients from southwest China with sporadic CHD were studied, including 121 patients with ventricular septal defect (VSD), 24 with atrial septal defect (ASD), 12 with tetralogy of fallot (TOF), six VSD cases with TOF, two cases with patent ductus arteriosus (PDA), and two VSD cases with ASD. 22q11.2, GATA4, NKX2‐5, TBX5, BMP4, and CRELD1 regions were screened using MLPA and copy number variation sequencing (CNV‐Seq). Results: A 2.5‐2.8 Mb deletion in the 22q11.2 region was identified in 5 patients with CHD. Two of these patients were diagnosed with VSD, while two had VSD and ASD, and the other had TOF. 5 patients correspond to the same classical DiGeorge syndrome. A 0.86 Mb duplication in the 22q11.2 region was identified in a PDA patient, whom was without extracardiac symptoms. Conclusion: These data suggest that copy number variation in the 22q11.2 region is common in CHD patients in southwest China. Regardless of the presence or absence of extracardiac symptoms, results also indicate that it is necessary to perform prenatal screening for CHD.